Euro area labour markets and the crisis (European Central Bank (ECB), 2012)
Between the start of the economic and financial crisis in 2008, and early 2010, almost four million jobs were lost in the euro area. Employment began to rise again in the first half of 2011, but declined once more at the end of that year and remains at around three million workers below the pre-crisis level. However, in comparison with the severity of the fall in GDP, employment adjustment has been relatively muted at the aggregate euro area level, mostly due to significant labour hoarding in several euro area countries. While the crisis has, so far, had a more limited or shorter-lived impact in some euro area countries, in others dramatic changes in employment and unemployment rates have been observed and, indeed, more recent data tend to show the effects of a reintensification of the crisis. The main objectives of this report are: (a) to understand the notable heterogeneity in the adjustment observed across euro area labour markets, ascertaining the role of the various shocks, labour market institutions and policy responses in shaping countries' labour market reactions; and (b) to analyse the medium-term consequences of these labour market developments. With these objectives in mind, the SIR Task Force has carried out several specific exercises (e.g. it has conducted a questionnaire among euro area National Central Bank (NCB) experts on main policy measures adopted since the start of the crisis; it has updated a previous Wage Dynamics Network (WDN) questionnaire on wage bargaining institutions in euro area countries; and it has computed worker flows series from Labour Force Survey (LFS) microdata available at most euro area NCBs).
Keywords: E42; F15; F33; F41; 330; crisis; Employment; Euro area countries; labour demand; labour supply; participation; Unemployment